Surface chlorophyll anomalies induced by mesoscale eddy-wind interactions in the northern Norwegian Sea - Dong, Huizi; Zhou, Meng; Raj, Roshin P.; Smith Jr, Walker O.; Basedow, Suennje L.; Ji, Rubao; Ashjian, Carin; Zhang, Zhaoru; Hu, Ziyuan (Frontiers in Marine Science, 2022)
The substantial productivity of the northern Norwegian Sea is closely related to its strong mesoscale eddy activity, but how eddies affect phytoplankton biomass levels in the upper ocean through horizontal and vertical transport-mixing has not been well quantified. To assess mesoscale eddy induced ocean surface chlorophyll-a concentration (CHL) anomalies and modulation of eddy-wind interactions in the region, we constructed composite averaged CHL and wind anomalies from 3,841 snapshots of anticyclonic eddies (ACEs) and 2,727 snapshots of cyclonic eddies (CEs) over the period 2000-2020 using satellite altimetry, scatterometry, and ocean color products. Results indicate that eddy pumping induces negative (positive) CHL anomalies within ACEs (CEs), while Ekman pumping caused by wind-eddy interactions induces positive (negative) CHL anomalies within ACEs (CEs). Eddy-induced Ekman upwelling plays a key role in the unusual positive CHL anomalies within the ACEs and results in the vertical transport of nutrients that stimulates phytoplankton growth and elevated productivity of the region. Seasonal shoaling of the mixed layer depth (MLD) results in greater irradiance levels available for phytoplankton growth, thereby promoting spring blooms, which in combination with strong eddy activity leads to large CHL anomalies in May and June. The combined processes of wind-eddy interactions and seasonal shallowing of MLD play a key role in generating surface CHL anomalies and is a major factor in the regulation of phytoplankton biomass in the northern Norwegian Sea.